PM2.5 and PM10 Concentrations at Indoor and Outdoor in Industrial Area - Sumeru, Kasni; Novianti, Senia Firlania; Firdaus Bin Sukri, Mohamad (Jurnal Internasional Penelitian Teknologi Terapan, 2020)
This study examines the total concentration of particulate matter (PM) in Banjaran, an industrial sub-district located in the south of Bandung. Sampling was conducted using the gravimetric method with a mini particle counter measuring instrument, known as CEM DT-96. Sampling was carried out at a house and a school in 24-hours and five days of working hours. The results show that concentration of PM either during indoor or outdoor condition can be affected by activity, air temperature, air relative humidity, air ventilation area, and particulate deposition rate. In addition, air quality for industrial area was categorized as unhealthy. It is due to PM concentrations exceeding air pollution quality standards as highlighted by Environmental Protection Agency.